Mandarin Swear Words Used by Chinese: A Descriptive Qualitative Study - Hayuni, Nyoman Tri; Budasi, I Gede; Ramendra, Dewa Putu (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
Swear words, while often considered taboo, have played a significant role in human communication. This study aimed to identify the Mandarin swear words used by Chinese speakers, analyze their forms, references, and functions. The research was conducted using a descriptive qualitative design. Primary data were collected through document analysis and interviews. The researcher acted as the main instrument, supported by document analysis sheets and interview guides. Three informants were selected based on predetermined criteria. The data were analyzed descriptively using the theory of Miles and Huberman (1984). The results of the study showed that there were 34 Mandarin swear words used by Chinese speakers. In terms of form, 13 were classified as words, consisting of 1 monomorphemic word and 12 polymorphemic words; 12 were phrases, and 9 were clauses. With regard to their references, five categories were identified: sex (5), excrement (2), animal names (2), mental illness (3), and personal background (5). Furthermore, five functions of Mandarin swear words were found: expressing emotion (8), drawing attention (5), social group identity (2), aggression (18), and regressive (1). These findings highlight the various ways in which swear words are employed in Mandarin, revealing their communicative purposes and sociolinguistic relevance.